Composite material containing porous carbon and sodium ferric sulfate as well as preparation method and application of composite material
By using a composite material of porous carbon and sodium ferrosulfate in sodium ion capacitors, the problem of insufficient energy density and conductivity of sodium ion capacitors is solved, and higher rate performance and suitable for industrial production are achieved.
Patent Information
- Application Number
- CN202310867587.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-15
- Publication Date
- 2025-01-17
AI Technical Summary
The porous carbon cathode material of existing sodium ion capacitors is not high in energy density, poor conductivity of sodium ferric sulfate and slow sodium ions transfer, resulting in insufficient rate performance.
By distributing sodium ferrosulfate on the pore neutralization surface of porous carbon, a composite material of porous carbon and sodium ferrosulfate is used, combined with specific preparation methods, such as impregnation and calcination under an alkaline atmosphere, to form a high specific surface area and appropriate pore size Distributed composite materials to improve conductivity and sodium ion transport efficiency.
It significantly improves the specific capacity and energy density of the cathode of the sodium ion capacitor, improves the rate performance and conductivity of the material, and is suitable for industrial production.
Smart Images

Figure CN119324126A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy, and relates to a positive electrode material for a sodium ion capacitor and a preparation method thereof, and in particular to a positive electrode material comprising sodium ferric sulfate and a preparation method thereof. Background Art
[0002] The proportion of renewable energy represented by wind power and solar energy is increasing, but intermittent renewable energy needs to be coupled with energy storage systems to be connected to the grid. In recent years, electrochemical energy storage technology has developed rapidly. Among them, supercapacitors have the advantages of high charging and discharging power, long cycle life, and a wide operating temperature range. They can be used to smooth out grid fluctuations caused by renewable energy. However, the energy density of traditional double-layer supercapacitors is not high and the application cost is relatively high. If relatively cheap and abundant sodium-ion batteries are combined with double-layer capacitors to form sodium-ion capacitors, it is expected that the energy density of the device can be greatly improved.
[0003] The positive electrode of the sodium ion capacitor uses the porous carbon material of the double-layer capacitor, relying on the high specific surface area to adsorb ions for energy storage. The negative electrode uses the amorphous carbon material of the sodium ion battery, relying on the embedding and release of sodium ions inside the negative electrode for energy storage. The specific capacity of the porous carbon positive electrode material is the main factor determining the energy density of the sodium ion capacitor.
[0004] At present, the reversible specific capacity of porous carbon positive electrode of sodium ion capacitor is generally 30-70 mAh / g, which is mainly limited by the specific surface area of the material. In addition, the high porosity caused by the high specific surface area is not conducive to energy density and conductivity. The composite of porous carbon and sodium iron sulfate can effectively improve the energy density. Loading sodium iron sulfate in the pores of porous carbon can effectively improve its electrochemical performance. Therefore, the pore design of porous carbon is crucial to the electrochemical performance of the composite material.
[0005] CN115020681A discloses a carbon-wrapped sodium ferric sulfate positive electrode material, including an active sodium ferric sulfate material and a carbon-based wrapping material. The carbon-based wrapping material adopts one of carbon nanotubes, carbon fibers, reduced graphene oxide, graphene, conductive carbon black, and activated carbon, and the mass ratio of the carbon-based wrapping material is 0.01-20%. The present invention effectively solves the technical difficulties in the practical application of polyanionic iron-based sulfate positive electrode materials for sodium ion batteries, and overcomes the problems of low sodium storage gram capacity, continuous decrease in working potential, poor cycle stability, poor rate performance and low-temperature working performance. However, this method fails to reduce the particle size of sodium ferric sulfate to less than 100 nanometers, and the rate performance is insufficient.
[0006] CN109192982A discloses a method for synthesizing sodium ferric sulfate positive electrode material, the steps are as follows: first, Na2SO4 and FeSO4·7H2O are mixed, a carbon source is added to the mixture, the mass of the carbon source is 0.75-1.5%wt of the mass of the mixture, after mixing evenly, high-energy ball milling is performed for several times, each time for 20-30 minutes, to obtain highly dispersed uniform powder; then the uniform powder after ball milling is calcined for 10-30 hours in an inert atmosphere of high-purity argon at 320-380°C, the product is cooled to room temperature with the furnace, and then manually ground for 3-10 minutes until no large particles are visible to the naked eye, which is the final material. The synthesis method of the present invention is simple and the operation process is short, but the method fails to reduce the particle size of sodium ferric sulfate to less than 100 nanometers, the conductive network is not well developed, and the material rate performance is insufficient. Summary of the invention
[0007] In view of the need for high specific capacity sodium ion capacitor positive electrode materials, the main purpose of the present invention is to provide a composite material comprising porous carbon and sodium ferric sulfate and its preparation method and application. When the composite material comprising porous carbon and sodium ferric sulfate is used as a positive electrode material, the positive electrode specific capacity of the corresponding sodium ion capacitor can be increased by more than 20%, and the energy density of the sodium ion capacitor can also be increased, solving the problems of poor electronic conductivity of sodium ferric sulfate and slow sodium ion transmission.
[0008] A first aspect of the present invention provides a composite material comprising porous carbon and sodium ferric sulfate, wherein the composite material comprises porous carbon and sodium ferric sulfate, wherein the sodium ferric sulfate is distributed in the pores and on the outer surface of the porous carbon, wherein the content of the porous carbon is 20wt% to 80wt%, preferably 30wt% to 60wt%, based on the total weight of the composite material.
[0009] Preferably, as some specific embodiments, in the composite material comprising porous carbon and sodium iron sulfate, the specific surface area of the composite material is 1200 to 3500 m 2 / g, preferably 2200 to 3000 m 2 / g.
[0010] Preferably, as some specific embodiments, in the above-mentioned composite material including porous carbon and sodium iron sulfate, the pore size distribution of the composite material has the following characteristics: the pore volume occupied by its mesopores is 10% to 50% of the total pore volume of micropores and mesopores, and more preferably 15% to 30%; wherein the pore diameter of the mesopores is 2 to 50 nm, and the pore diameter of the micropores is less than 2 nm.
[0011] Preferably, as some specific embodiments, in the above-mentioned composite material including porous carbon and sodium ferric sulfate, the characteristic diffraction peak of sodium ferric sulfate measured by X-ray diffraction method, and its statistical crystal size calculated by Scherrer formula is 2 to 30 nm, preferably 4 to 15 nm.
[0012] A second aspect of the present invention provides a method for preparing a composite material comprising porous carbon and sodium iron sulfate, comprising the following steps:
[0013] (1) mixing an iron-containing compound, a sodium-containing compound, a sulfate-containing compound, and a solvent under mixing conditions to obtain a first material stream;
[0014] (2) mixing the porous carbon with the first material flow obtained in step (1) to obtain a second material flow;
[0015] (3) The second material stream obtained in step (2) is dried and calcined to obtain a composite material.
[0016] Preferably, as some specific embodiments, in the preparation method of the composite material comprising porous carbon and sodium iron sulfate, the iron-containing compound in step (1) is an iron salt, which may be an inorganic salt and / or an organic salt. The specific iron-containing compound may be selected from one or more of ferric chloride, ferric nitrate, ferric sulfate, ferrous oxalate, ferrous acetate, ferrous oxalate, and ferrous ammonium sulfate, preferably ferric chloride.
[0017] Preferably, as some specific embodiments, in the preparation method of the composite material comprising porous carbon and sodium ferric sulfate, the sulfate-containing compound in step (1) is selected from one or more of sulfuric acid, sodium bisulfate, sodium sulfate, ferrous sulfate, ammonium sulfate, ammonium bisulfate, ammonium sulfate, and sodium ammonium sulfate, preferably sulfuric acid.
[0018] Preferably, as some specific embodiments, in the preparation method of the composite material comprising porous carbon and sodium iron sulfate, the sodium-containing compound in step (1) is an inorganic sodium salt and / or an organic sodium salt. More specifically, the sodium-containing compound can be selected from one or more of sodium chloride, sodium nitrate, sodium nitrite, sodium sulfate, sodium hydroxide, sodium bromide, sodium ethoxide, sodium methoxide, sodium acetate, sodium formate, sodium oxalate, sodium oleate, and sodium bicarbonate, preferably one or more of sodium chloride, sodium nitrate, and sodium acetate.
[0019] Preferably, as some specific embodiments, in the preparation method of the composite material including porous carbon and sodium iron sulfate, the solvent in step (1) is water and / or an organic solvent, and the organic solvent is an alcohol solvent, specifically one or more of ethanol, acetone, methanol, ethylene glycol, n-propanol, and isopropanol.
[0020] Preferably, as some specific embodiments, in the preparation method of the above-mentioned composite material including porous carbon and sodium ferric sulfate, the amount of iron-containing compound, sodium-containing compound and sulfate-containing compound is determined according to the molecular composition of sodium ferric sulfate based on the molar ratio, wherein the molecular formula of sodium ferric sulfate is Na2Fe2(SO4)3.
[0021] Preferably, as some specific embodiments, in the preparation method of the composite material comprising porous carbon and sodium iron sulfate, the porous carbon in step (2) comprises two levels of pores, namely, micropores (micropores having a pore size of less than 2 nm) and mesopores (mesopores having a pore size of 2 to 50 nm), wherein the pore volume of the mesopores is 20% to 70%, preferably 30% to 50%, of the total pore volume of micropores and mesopores. The porous carbon is in powder form, and the particle size of the porous carbon is 1 to 100 μm, preferably 3 to 20 μm.
[0022] Preferably, as some specific embodiments, in the preparation method of the composite material including porous carbon and sodium iron sulfate, the mixing in step (2) can be carried out by impregnation, and the first material flow can be impregnated with the powdered porous carbon in multiple times, and the first material flow is absorbed by the rich pores of the porous carbon, and the mass ratio of the porous carbon to the first material flow is 1:4 to 4:1.
[0023] Preferably, as some specific embodiments, in the preparation method of the above-mentioned composite material including porous carbon and sodium iron sulfate, the drying in step (3) is generally carried out under the following conditions: the drying temperature is 60-150°C, and the drying time is 1-24h; preferably the drying temperature is 80-120°C, and the drying time is 2-12h.
[0024] Preferably, as some specific embodiments, in the preparation method of the composite material including porous carbon and sodium iron sulfate, the calcination in step (3) is usually carried out under the following conditions: the calcination temperature is 200-500°C, and the calcination time is 0.5-8 hours; preferably the calcination temperature is 300-400°C; the calcination time is 1-4 hours. The calcination is carried out in the presence of an inert atmosphere or a reducing atmosphere, the inert atmosphere is nitrogen and / or an inert gas, and the inert gas is at least one of helium, argon, and neon; the reducing atmosphere is a mixed gas of hydrogen and an inert atmosphere, and the volume content of hydrogen in the mixed gas is 1-50%; the inert atmosphere is nitrogen and / or an inert gas.
[0025] Preferably, as some specific embodiments, in the preparation method of the composite material comprising porous carbon and sodium iron sulfate, the second material stream obtained in step (2) is preferably pretreated first, and the pretreatment is to treat the second material stream obtained in step (2) in the presence of an alkaline atmosphere, and the material stream obtained after the treatment is further dried and calcined to obtain a composite material; the alkaline atmosphere can be at least one of ammonia, ammonium carbonate, ammonium bicarbonate, and ethylenediamine; preferably, it is carried out in the presence of an ammonia atmosphere; the treatment temperature is 50 to 160°C, preferably 60 to 120°C.
[0026] The third aspect of the present invention provides a composite material comprising porous carbon and sodium iron sulfate, or a composite material comprising porous carbon and sodium iron sulfate obtained by the above preparation method, which can be used as a positive electrode active material of a sodium ion capacitor.
[0027] A fourth aspect of the present invention provides a sodium ion battery, comprising the composite material comprising porous carbon and sodium ferric sulfate, or the composite material comprising porous carbon and sodium ferric sulfate prepared by the above method.
[0028] The main advantages and technical effects of the composite material including porous carbon and sodium iron sulfate and the preparation method thereof provided by the present invention are embodied in the following aspects:
[0029] 1. The conductivity of sodium ferric sulfate is extremely low, so an efficient conductive network is required to enable sodium ferric sulfate to exert all its electrochemical properties. Sodium ferric sulfate is synthesized by in-situ hydrolysis in a porous carbon three-dimensional conductive carrier, so that sodium ferric sulfate and conductive carbon materials are evenly dispersed on a scale of several nanometers, effectively solving the problem of poor conductivity of sodium ferric sulfate. The sodium ferric sulfate synthesized by traditional solid-phase method, precipitation method and sol-gel method has large particle size and can only disperse carbon and sodium ferric sulfate on a scale of hundreds of nanometers. Part of the sodium ferric sulfate cannot be used during the charge and discharge process, resulting in low reversible specific capacity.
[0030] 2. The present invention makes the ions of sodium iron sulfate dispersed evenly at the atomic level in the product by configuring the precursor solution, which is difficult to achieve by the traditional solid phase method. Although the ion distribution of the precipitation method is relatively uniform, the solubility product of each ion is different, and the ion distribution of the particle content is uneven. The raw materials used in the sol-gel method are relatively expensive and not suitable for industrial production. The raw materials of the iron source, sodium source and sulfate of the present invention are relatively cheap and suitable for industrial production.
[0031] 3. The porous carbon-sodium iron sulfate composite material provided by the present invention can be calcined at a relatively low temperature, so that the crystalline state is amorphous, and the sodium ion transmission can be free from the constraints of the lattice, thereby improving the rate performance of the material.
[0032] 4. In the method for preparing the porous carbon-sodium iron sulfate composite material provided by the present invention, the rate performance of the material can be improved by pretreating the porous carbon powder impregnated with the sodium iron sulfate solution in an alkaline atmosphere. Pretreatment in an alkaline environment can convert the precursor solution into a precursor in situ and improve the dispersion of the sodium iron sulfate particles, thereby improving the rate performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The XRD comparison diagrams of the samples obtained in Example 1 of the present invention (before the porous carbon is loaded with sodium ferric sulfate) and Comparative Example 1 (after the porous carbon is loaded with sodium ferric sulfate) are shown.
[0034] Figure 2 It is a constant current charge and discharge curve diagram of the porous carbon sample before loading in Example 1 of the present invention and the porous carbon loaded sodium iron sulfate sample obtained in Example 1.
[0035] Figure 3 1 is a cyclic voltammogram of the porous carbon sample before loading in Example 1 of the present invention and the porous carbon loaded with sodium ferric sulfate sample obtained in Example 1. DETAILED DESCRIPTION
[0036] The technical content and effects of the present invention are further illustrated below in conjunction with embodiments, but the present invention is not limited thereby.
[0037] The specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings and specific embodiments. However, it should be pointed out that the protection scope of the present invention is not limited by these specific implementation modes, but is determined by the claims.
[0038] In the context of this specification, pore volume, specific surface area and pore size distribution are measured using a low temperature nitrogen adsorption method.
[0039] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight.
[0040] In the context of this specification, any two or more embodiments of the present invention may be arbitrarily combined, and the technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0041] Example 1
[0042] Weigh 82.0g of sodium acetate and dissolve it in 100mL of deionized water. Add 270g of ferric chloride hexahydrate and 150g of 98% sulfuric acid and dilute to 500mL to prepare a precursor solution. Weigh 200g of petroleum coke-based porous carbon powder (specific surface area 2856m 2 / g, pore volume 1.33cm 3 / g, mesoporous volume ratio of 33%, D50 particle size 6μm), put it in an oven and dry it at 100℃ for 5 hours. Add 500mL of precursor solution dropwise to the porous carbon powder, mix the two evenly, and dry the mixture in an oven at 100℃ for 5 hours. Put the mixture in a tube furnace and calcine it at 350℃ for 2 hours under argon atmosphere. The product is marked as PC / NFS-1, and the XRD pattern of the sample is shown in Figure 1 .
[0043] Combination Figure 1 According to the Scherrer formula (D = 0.89λ / (B cosθ), D is the grain size (nm), B is the half-height width of the diffraction peak, θ is the Bragg angle, λ is the wavelength of the X-ray used In Example 1, the sodium ferric sulfate is in an amorphous state, and the sodium ion transmission is not bound by the lattice, which is beneficial to the rate performance of the sodium ferric sulfate.
[0044] pass Figure 2 It can be seen that the reversible specific capacity of the pure porous carbon sample before loading is 79.7 mAh / g, and the reversible specific capacity of the porous carbon loaded with sodium iron sulfate sample is 92.2 mAh / g. The specific capacity is increased by 15% after loading with sodium iron sulfate.
[0045] pass Figure 3 It can be seen that the pure porous carbon sample before loading presents a rectangular curve, and the porous carbon loaded sodium iron sulfate sample has a bulging peak at 2.6V, which corresponds to the redox peak caused by the insertion and extraction of sodium iron sulfate, indicating that the increase in the reversible specific capacity of the sample in Example 1 comes from the loading of sodium iron sulfate.
[0046] Example 2
[0047] Weigh 58.4g of sodium chloride and dissolve it in 100mL of deionized water. Add 270g of ferric chloride hexahydrate and 150g of 98% sulfuric acid and dilute to 500mL to prepare a precursor solution. Weigh 200g of petroleum coke-based porous carbon powder (specific surface area 2856m 2 / g, pore volume 1.33cm 3 / g, mesoporous volume accounts for 33%, D50 particle size 6μm), put it in an oven and dry it at 120℃ for 2 hours. Add 500mL of precursor solution dropwise to the porous carbon powder and mix the two evenly. Take 500mL of 25wt% concentrated ammonia water and put it in beaker A, put the mixture in beaker B, put the two beakers in a sealed plastic bucket, put the plastic bucket in a 100℃ blast oven for 12 hours, take out beaker B, put it in a 120℃ blast oven for 3 hours, and then put it in a tubular furnace and calcine it at 350℃ for 2 hours under an argon atmosphere. The product is marked as PC / NFS-N-1.
[0048] Example 3
[0049] Weigh 58.4g of sodium chloride and dissolve it in 100mL of deionized water. Add 404g of ferric nitrate nonahydrate and 150g of 98wt% sulfuric acid. Add deionized water to make the volume to 600mL to prepare a precursor solution. Weigh 200g of petroleum coke-based porous carbon powder (specific surface area 2117m 2 / g, pore volume 1.13cm 3 / g, mesoporous volume ratio of 20%, D50 particle size 8μm), put it in an oven and dry it at 100℃ for 5 hours. 600mL of precursor solution was added dropwise to the porous carbon powder, the two were evenly mixed, and the mixture was dried in an oven at 100℃ for 5 hours. The mixture was placed in a tube furnace and calcined at 350℃ for 2 hours under an argon atmosphere. The product is marked as PC / NFS-2.
[0050] Example 4
[0051] Weigh 142.0g of sodium sulfate, dissolve it in 200mL of deionized water, add 270.3g of ferric chloride hexahydrate, add 100g of 98wt% phosphoric acid, stir, add 50mL of ethanol, and dilute to 650mL with deionized water to prepare a precursor solution. Weigh 200g of petroleum coke-based porous carbon powder (specific surface area 2856m 2 / g, pore volume 1.33cm 3 / g, mesoporous volume ratio of 33%, D50 particle size 6μm), put it in an oven and dry it at 100℃ for 5 hours. 650mL of the precursor solution was added dropwise to the porous carbon powder, the two were evenly mixed, and put it in a tube furnace and calcined at 400℃ for 3 hours under argon atmosphere. The product is marked as PC / NFS-3.
[0052] Example 5
[0053] Weigh 58.4g of sodium chloride, dissolve it in 100mL of deionized water, add 404g of ferric nitrate nonahydrate, add 150g of 98wt% phosphoric acid, and dilute to 600mL with deionized water to prepare a precursor solution. Weigh 200g of petroleum coke-based porous carbon powder (specific surface area 2856m 2 / g, pore volume 1.33cm 3 / g, mesoporous volume accounts for 33%, D50 particle size 6μm), put it in an oven and dry it at 100°C for 5 hours. Add 400mL of precursor solution dropwise to the porous carbon powder, mix the two evenly, and dry the mixture in a 100°C oven for 5 hours. Take 300g of ammonium bicarbonate powder and put it in beaker A, put the mixture in beaker B, put the two beakers in a sealed plastic bucket, put the plastic bucket in a 100°C blast oven for 12 hours, take out beaker B, and after 6 hours in a 100°C blast oven, put the mixture in a tubular furnace and calcine it at 300°C for 1 hour in an atmosphere of 90% argon / 10% hydrogen by volume. The product is marked as PC / NFS-N-2.
[0054] Example 6
[0055] Weigh 136.1 g of sodium acetate trihydrate, dissolve it in 100 mL of deionized water, add 404 g of ferric nitrate nonahydrate, add 172.7 g of ammonium hydrogen sulfate, and dilute to 600 mL with deionized water to prepare a precursor solution. Weigh 200 g of petroleum coke-based porous carbon powder (specific surface area 2856 m 2 / g, pore volume 1.33cm 3 / g, mesoporous volume ratio of 33%, D50 particle size 6μm), put it in an oven and dry it at 100℃ for 5 hours. 600mL of precursor solution was added dropwise to the porous carbon powder, and the two were evenly mixed. After 6 hours in a 100℃ forced air oven, it was placed in a tube furnace and calcined at 350℃ for 2 hours under argon atmosphere. The product was marked as PC / NFS-4.
[0056] Example 7
[0057] Weigh 142.0g of sodium sulfate and dissolve it in a mixed solution of 100mL of deionized water and 100mL of ethanol, add 404g of ferric nitrate nonahydrate, add 150g of 98wt% sulfuric acid, and finally dilute to 600mL with water to prepare a precursor solution. Weigh 300g of petroleum coke-based porous carbon powder (specific surface area 2531m 2 / g, pore volume 1.26cm 3 / g, mesoporous volume ratio of 25%, D50 particle size 7μm), put it in an oven and dry it at 100℃ for 5 hours. 600mL of precursor solution was added dropwise to the porous carbon powder, the two were evenly mixed, and the mixture was dried in an oven at 140℃ for 4 hours. The mixture was placed in a tube furnace and calcined at 350℃ for 2 hours under an argon atmosphere. The product is marked as PC / NFS-5.
[0058] Comparative Example 1
[0059] Weigh 58.4g of sodium chloride and dissolve it in 100mL of deionized water. Add 270g of ferric chloride hexahydrate and 150g of 98% sulfuric acid and adjust the volume to 600mL to prepare a precursor solution. Weigh 200g of acetylene black powder (specific surface area 10m 2 / g, pore volume can be ignored), put it in an oven and dry it at 100°C for 5 hours. 600mL of the precursor solution was added dropwise to the petroleum coke-based porous carbon powder, the two were evenly mixed, and the mixture was dried in an oven at 100°C for 5 hours. The mixture was placed in a tube furnace and calcined at 350°C for 2 hours under an argon atmosphere. The product is marked as C / NFS-1.
[0060] Comparative Example 2
[0061] Weigh 61.5g of sodium acetate and dissolve it in 100mL of deionized water. Add 404g of ferric nitrate nonahydrate and 150g of 98wt% sulfuric acid and adjust the volume to 600mL to prepare a precursor solution. Weigh 200g of acetylene black powder (specific surface area 10m 2 / g, pore volume can be ignored), put it in an oven and dry it at 100°C for 5 hours. Add 600mL of precursor solution dropwise into porous carbon powder and mix the two evenly. Take 500mL of 25% concentrated ammonia water and put it in beaker A, put the mixture in beaker B, put the two beakers in a sealed plastic bucket, put the plastic bucket in a 100°C forced air oven for 12 hours, take out beaker B, put it in a 100°C forced air oven for 6 hours, and then put it in a tube furnace and calcine it at 350°C for 2 hours under an argon atmosphere. The product is marked as C / NFS-N-1.
[0062] Comparative Example 3
[0063] 134 g of sodium oxalate, 400 g of ferric sulfate and 35 g of sucrose were weighed and mixed, ball-milled at 500 rpm for 12 hours, and calcined at 350°C for 5 hours in a tube furnace under an argon atmosphere. The product was mixed with 200 g of petroleum coke-based porous carbon powder (specific surface area 2856 m 2 / g, pore volume 1.33cm 3 / g, mesopore volume ratio is 33%, D50 particle size is 6μm) and the product is marked as PC-NFS-1.
[0064] Comparative Example 4
[0065] 134 g of sodium oxalate, 400 g of ferrous sulfate and 35 g of sucrose were weighed and mixed, and ball milled at 500 rpm for 12 h. The product was mixed with 200 g of petroleum coke-based porous carbon powder (specific surface area 2856 m 2 / g, pore volume 1.33cm 3 / g, mesoporous volume ratio of 33%, D50 particle size 6μm) were mixed, 500mL of 25wt% concentrated ammonia water was placed in beaker A, the mixture was placed in beaker B, the two beakers were placed in a sealed plastic bucket, the plastic bucket was placed in a 100℃ forced air oven for 12 hours, and then beaker B was taken out. The mixture was placed in a tube furnace and calcined at 350 degrees for 2 hours under an argon atmosphere. The product was marked as PC-NFS-N-1.
[0066] Evaluation test:
[0067] Electrochemical test method: Mix the product, acetylene black (conductive agent) and polyvinylidene fluoride (binder) in N-methylpyrrolidone at a mass ratio of 8:1:1 to prepare a slurry, stir thoroughly and apply it on aluminum foil, and cut the aluminum foil into 12mm discs. Put the cut discs in the positive electrode shell of the button battery, with the side loaded with the product facing up, and add a polypropylene diaphragm with a diameter of 19mm and a metal sodium disc with a diameter of 15.6mm on the discs in turn, and then put the gasket and spring of the button battery respectively, cover the negative electrode shell and package it into a button battery. The reversible specific capacity of the button battery at current densities of 0.1A / g and 2A / g was tested on the Xinwei battery charge and discharge tester, and the cyclic voltammetry curve was tested on the Swiss Metrohm electrochemical workstation.
[0068] Table 1. Reversible specific capacity of samples at different current densities
[0069]
[0070]
Claims
1. A composite material comprising porous carbon and sodium iron sulfate, characterized in that: The composite material comprises porous carbon and sodium ferric sulfate, wherein the sodium ferric sulfate is distributed in the pores and on the outer surface of the porous carbon, wherein the content of the porous carbon is 20wt% to 80wt%, preferably 30wt% to 60wt%, based on the total weight of the composite material.
2. The composite material comprising porous carbon and sodium iron sulfate according to claim 1, characterized in that: The specific surface area of the composite material is 1200~3500 m 2 / g, preferably 2200 to 3000 m 2 / g.
3. The composite material comprising porous carbon and sodium iron sulfate according to claim 1, characterized in that: The pore size distribution of the composite material has the following characteristics: the pore volume occupied by the mesopores is 10% to 50% of the total pore volume of the micropores and mesopores, and more preferably 15% to 30%; the pore size of the mesopores is 2 to 50 nm, and the pore size of the micropores is less than 2 nm.
4. The composite material comprising porous carbon and sodium iron sulfate according to claim 1, characterized in that: The characteristic diffraction peak of sodium iron sulfate measured by X-ray diffraction method is 2 to 30 nm, preferably 4 to 15 nm, and its statistical crystal size is calculated by Scherrer formula.
5. A method for preparing a composite material comprising porous carbon and sodium iron sulfate, comprising the following steps: (1) mixing an iron-containing compound, a sodium-containing compound, a sulfate-containing compound, and a solvent under mixing conditions to obtain a first material stream; (2) mixing the porous carbon with the first material flow obtained in step (1) to obtain a second material flow; (3) The second material stream obtained in step (2) is dried and calcined to obtain a composite material.
6. The method for preparing the composite material comprising porous carbon and sodium iron sulfate according to claim 5, characterized in that: The iron-containing compound in step (1) is an iron salt, and the iron salt is an inorganic salt and / or an organic salt.
7. The method for preparing a composite material comprising porous carbon and sodium iron sulfate according to claim 5 or 6, characterized in that: The iron-containing compound in step (1) is selected from one or more of ferric chloride, ferric nitrate, ferric sulfate, ferric oxalate, ferric acetate, ferrous oxalate, and ammonium ferrous sulfate, preferably ferric chloride.
8. The method for preparing the composite material comprising porous carbon and sodium iron sulfate according to claim 5, characterized in that: The sulfate-containing compound in step (1) is selected from one or more of sulfuric acid, sodium bisulfate, sodium sulfate, ferrous sulfate, ammonium sulfate, ammonium bisulfate, ammonium sulfate, and sodium ammonium sulfate, preferably sulfuric acid.
9. The method for preparing the composite material comprising porous carbon and sodium iron sulfate according to claim 5, characterized in that: The sodium-containing compound in step (1) is an inorganic sodium salt and / or an organic sodium salt.
10. The method for preparing a composite material comprising porous carbon and sodium iron sulfate according to claim 5 or 9, characterized in that: The sodium-containing compound in step (1) is selected from one or more of sodium chloride, sodium nitrate, sodium nitrite, sodium sulfate, sodium hydroxide, sodium bromide, sodium ethoxide, sodium methoxide, sodium acetate, sodium formate, sodium oxalate, sodium oleate, and sodium bicarbonate, preferably one or more of sodium chloride, sodium nitrate, and sodium acetate.
11. The method for preparing the composite material comprising porous carbon and sodium iron sulfate according to claim 5, characterized in that: The solvent in step (1) is water and / or an organic solvent, the organic solvent is an alcohol solvent, and the alcohol solvent is one or more of ethanol, acetone, methanol, ethylene glycol, n-propanol, and isopropanol.
12. The method for preparing the composite material comprising porous carbon and sodium iron sulfate according to claim 5, characterized in that: Based on the molar ratio, the amount of the iron-containing compound, the sodium-containing compound, and the sulfate-containing compound is determined according to the molecular composition of sodium ferric sulfate, wherein the molecular formula of sodium ferric sulfate is Na2Fe2(SO4)3.
13. The method for preparing the composite material comprising porous carbon and sodium iron sulfate according to claim 5, characterized in that: The porous carbon in step (2) includes two levels of pores, micropores and mesopores, wherein the pore volume of the mesopores is 20% to 70%, preferably 30% to 50%, of the total pore volume of the micropores and mesopores; the porous carbon is in powder form, and the particle size of the porous carbon is 1 to 100 μm, preferably 3 to 20 μm.
14. The method for preparing the composite material comprising porous carbon and sodium iron sulfate according to claim 5, characterized in that: The mixing in step (2) is carried out by impregnation, wherein the first material flow is impregnated with the powdered porous carbon for multiple times, and the mass ratio of the porous carbon to the first material flow is 1:4 to 4:
1.
15. The method for preparing the composite material comprising porous carbon and sodium iron sulfate according to claim 5, characterized in that: The drying temperature in step (3) is 60-150° C., and the drying time is 1-24 h; preferably, the drying temperature is 80-120° C., and the drying time is 2-12 h.
16. The method for preparing the composite material comprising porous carbon and sodium iron sulfate according to claim 5, characterized in that: The calcination temperature in step (3) is 200-500° C., and the calcination time is 0.5-8 hours; preferably, the calcination temperature is 300-400° C., and the calcination time is 1-4 hours.
17. The calcination is carried out in an inert atmosphere or a reducing atmosphere, wherein the inert atmosphere is nitrogen and / or an inert gas, and the inert gas is at least one of helium, argon, and neon; the reducing atmosphere is a mixed gas of hydrogen and an inert atmosphere, and the volume content of hydrogen in the mixed gas is 1 to 50%; the inert atmosphere is nitrogen and / or an inert gas.
18. The method for preparing the composite material comprising porous carbon and sodium iron sulfate according to claim 5, characterized in that: The second material stream obtained in step (2) is first pretreated, wherein the pretreatment is to treat the second material stream obtained in step (2) in the presence of an alkaline atmosphere, and the material stream obtained after the treatment is further dried and calcined to obtain a composite material; the alkaline atmosphere is at least one of ammonia, ammonium carbonate, ammonium bicarbonate, and ethylenediamine; preferably ammonia; the treatment temperature is 50 to 160°C, preferably 60 to 120°C.
19. A composite material comprising porous carbon and sodium iron sulfate as claimed in any one of claims 1 to 4 or a composite material comprising porous carbon and sodium iron sulfate obtained by the preparation method as claimed in any one of claims 5 to 18 as a positive electrode active material of a sodium ion capacitor.
20. A sodium ion battery, comprising the composite material comprising porous carbon and sodium ferric sulfate as claimed in any one of claims 1 to 4 or the composite material comprising porous carbon and sodium ferric sulfate obtained by the preparation method as claimed in any one of claims 5 to 18.
Citation Information
Patent Citations
A synthetic method of sodium ferric sulfate positive electrode material
CN109192982A
Cited By
High-performance sodium ferric sulfate polyanion positive electrode material and preparation method thereof
CN119864415A